INVESTIGATION OF ENDOTHELIAL AND RENAL DYSFUNCTION IN PATIENTS WITH STABLE ANGINA PECTORIS AND ASSESSMENT OF THEIR RELATIONSHIP - Ergashova E.D.; Axmedov X.S.; Turgunova M. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Material and research methods. 42 patients with coronary heart disease (CHD) aged 45 to 70 years (mean age 63.5±4.5 years) were examined. The first group consisted of 22 people, including 15 men and 7 women (mean age of patients 56.4±7.5 years) with functional class II coronary heart disease and without kidney damage. The second group included 20 people (14 and 6 women), mean age 62.0±5.5 years, with functional class III ischemic heart disease and no primary kidney disease in men. 10 people of the first group and 16 people of the second group suffered from hypotonic 52 diseases, 8 and 12, respectively, history of diabetes. All patients underwent a general clinical examination with an assessment of the content of cystatin and calcium in the blood. The glomerular filtration rate calculates the plasma concentration of cystatin using the formula of Hoek et al. (2003): GFR [mL/min/1.73m2] = (80.35/cystatin C [mg/mL]) - 4.32.